(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: SARS-coronavirus-2 is a new virus infecting people and causing COVID-19 disease. The disease is causing a worldwide pandemic. Although some people never develop any signs or symptoms of disease when they are infected, other people are at very high risk for severe disease and death. Objective: If we’re able to intervene to prevent even some transmission, we can dramatically reduce the number of cases. And this is the public health goal for controlling COVID-19. Methods: This article initializes an approach for comparatively accurate values prediction of new cases and deaths for a particular day in order to be considered for preventive measures. The three statistical analysis methods considered for forecasting are Fbprophet, Moving average and the Autoregressive Integrated Moving Average algorithm. Results: The results obtained are in-line with the past and present trend of COVID-19 data collected from WHO website. Conclusion: The output is satisfactory for further consideration. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.85-96